Short-Term High-Fat Diet Fuels Colitis Progression in Mice Associated With Changes in Blood Metabolome and Intestinal Gene Expression - Wu, Zhen-Hua; Yang, Jing; Chen, Lei; Du, Chuang; Zhang, Qi; Zhao, Shan-Shan; Wang, Xiao-Yu; Yang, Jing; Liu, Yang; Cai, Demin; Du, Jian; Liu, Hui-Xin (Frontiers in Nutrition, 2022)
Clinical cases and animal experiments show that high-fat (HF) diet is involved in inflammatory bowel disease (IBD), but the specific mechanism is not fully clear. A close association between long-term HF-induced obesity and IBD has been well-documented. However, there has been limited evaluation of the impact of short-term HF feeding on the risk of intestinal inflammation, particularly on the risk of disrupted metabolic homeostasis. In this study, we analyzed the metabolic profile and tested the vulnerability of 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis after short-term HF feeding in mice. The results showed that compared with the control diet (CD), the fatty acid (FA), amino acid (AA), and bile acid (BA) metabolisms of mice in the HF group were significantly changed. HF-fed mice showed an increase in the content of saturated and unsaturated FAs and a decrease in the content of tryptophan (Trp). Furthermore, the disturbed spatial distribution of taurocholic acid (TCA) in the ileum and colon was identified in the HF group using matrix-assisted laser desorption/ionization-mass spectrometry imaging (MALDI-MSI). After HF priming, mice on TNBS induction were subjected to more severe colonic ulceration and histological damage compared with their CD counterparts. In addition, TNBS enema induced higher gene expressions of mucosal pro-inflammatory cytokines under HF priming conditions. Overall, our results show that HF may promote colitis by disturbing lipid, AA, and BA metabolic homeostasis and inflammatory gene expressions.